Recurrence and colon cancer‐specific death in patients with large bowel obstruction requiring urgent operation: a competing risks analysis. (23rd July 2021) - Adams, Katie; Chapuis, Pierre H.; Keshava, Anil; Rickard, Matthew J. F. X.; Stewart, Peter; Suen, Michael; Chan, Charles; Dent, Owen F.
Abstract: Aim: Clinical presentation with large bowel obstruction has been proposed as a predictor of poor long‐term oncological outcomes after resection for colorectal cancer. This study examines the association between obstruction and recurrence and cancer‐specific death after resection for colon cancer. Method: Consecutive patients who underwent resection for colon cancer between 1995 and 2014 were drawn from a prospectively recorded hospital database with all surviving patients followed for at least 5 years. The outcomes of tumour recurrence and colon cancer‐specific death were assessed by competing risks multivariable techniques with adjustment for potential clinical and pathological confounding variables. Results: Recurrence occurred in 271 of 1485 patients who had a potentially curative resection. In bivariate analysis, obstruction was significantly associated with recurrence [hazard ratio (HR) 2.23, CI 1.52–3.26, p  < 0.001] but this association became nonsignificant after adjustment for confounders (HR 1.53, CI 0.95–2.46, p  = 0.080). Colon cancer‐specific death occurred in 238 of 295 patients who had a noncurative resection. Obstruction was not significantly associated with cancer‐specific death (HR 1.02, CI 0.72–1.45, p  = 0.903). In patients who had a noncurative resection, the competing risks incidence of colon cancer‐specific death was not significantly greater in obstructed than in unobstructed patients (HR 1.02, CI 0.72–1.45, p  = 0.903). Conclusion: Whilst the immediate clinical challenge of an individual patient presenting with large bowel obstruction must be addressed by the surgeon, the patient's long‐term oncological outcomes are unrelated to obstruction per se.